Investigation on the Development of Asphalt Mixture Limit Criteria for Low-Temperature Cracking. Issue 1 (2016) - Cannone Falchetto, Augusto; Moon, Ki Hoon; Wistuba, Michael P.
This paper investigates the possibility of developing low-temperature limit criteria for asphalt mixtures, similar to what is currently available in the standard specification for asphalt binder. The research approach was based on extensive experimental work and on rheological modeling. Bending beam rheometer (BBR) tests were first performed on asphalt binders and asphalt mixtures, and the transformation developed by the research team of the Ecole Nationale des Travaux Publics de l'Etat (ENTPE) was used to analyze the experimental data. Creep stiffness results measured on long-term aged binder were used to predict the limiting asphalt mixture creep stiffness values, which were then compared with results available in the literature. The BBR creep values determined on short-term aged asphalt binder were used to predict the creep stiffness of the corresponding short-term aged asphalt mixtures. On the basis of these results, a range of limiting stiffness values was obtained. Because of large variations between the ENTPE predictions and the experimental results of the slope of the creep stiffness, a limiting value for the relaxation parameter—the m -value—cannot be recommended on the basis of the BBR data only. A comparison between the experimentally measured creep stiffness and the m -value obtained from BBR and indirect tensile tests shows a consistent trend in the low-temperature parameters.